PENGARUH KECERDASAN EMOSIONAL DAN SOSIAL TERHADAP SIKAP KEPEMIMPINAN SISWA KELAS XI MADRASAH ALIYAH MUWAHIDUN PATI - Widoarti, Annisa Nurjanah; Iman, Marsudi (Institut Daarul Qur'an Jakarta, Indonesia, 2022)
Adolescence is a determinant of an individual to step into the next stage of life, as this can affect the level of leadership. This study aims to (1) analyze the emotional intelligence of students of Madrasah Aliyah Muwahidun, (2) analyze the social intelligence of students of Madrasah Aliyah Muwahidun, and (3) analyze the leadership attitudes of students of Madrasah Aliyah Muwahidun, (4) analyze the effect of emotional and social intelligence on students' leadership attitudes of Madrasah Aliyah Muwahidun. This research used a quantitative approach and a population study. The population of the research was 61 students without a sample. The use of the SPSS 25.0 for windows application illustratespositive results. It means, there is an effect of emotional and social intelligence on the leadership attitude of class XI students of Madrasah Aliyah Muwahidun Pati with multiple linear regression tests which obtained a value of 0.00 < 0.005. This indicates that the effect is very significant and a determination value obtained is (R Square) 62.1%.